Optimization of Crude Palm Oil (CPO) Transportation Costs at PT Pelita Jaya Using a Transportation Model - Aqillah, Khayru; Garingging, Sartika; Azmi, Ulul; Tanjung, Ahmad Albar (PT Katersi Minar Permata, 2025)
As a company engaged in the field of CPO transportation , PT Pelita Jaya is also present in carrying out expeditions from the loading location to the destination (unloading). The company faces challenges in allocating a total of 900 tons of CPO from three PKS PT PTPN IV (Bah Jambi, Dolok Hilir, Pabatu) to three destination depots (PT MNA, PT KPBN, PT SMART) to achieve the lowest cost. This study aims to optimize the cost of Crude Palm Oil (CPO) transportation at PT Pelita Jaya. The type of data used is primary data with data collection through interviews and observations field. Researchers use a transportation model as a quantitative approach from Operations Research. Solutions are sought using three methods: Northwest Corner (NWC), Vogel's Approximation (VAM), and Stepping-Stone. with POM QM for Windows as tool supporters data processing . The results identified the optimal allocation that minimizes total costs: Bah Jambi PKS (340 tons) is allocated entirely to PT MNA; Dolok Hilir PKS (260 tons) is allocated entirely to PT SMART (260 tons); and Pabatu PKS (300 tons) is allocated to PT MNA (60 tons), PT KPBN (200 tons) and PT SMART (40 tons). The application of this model has proven successful in providing strategic recommendations to minimize logistics costs and improve distribution efficiency at PT Pelita Jaya.